2020
DOI: 10.1093/nar/gkaa289
|View full text |Cite
|
Sign up to set email alerts
|

The human telomeric nucleosome displays distinct structural and dynamic properties

Abstract: Telomeres protect the ends of our chromosomes and are key to maintaining genomic integrity during cell division and differentiation. However, our knowledge of telomeric chromatin and nucleosome structure at the molecular level is limited. Here, we aimed to define the structure, dynamics as well as properties in solution of the human telomeric nucleosome. We first determined the 2.2 Å crystal structure of a human telomeric nucleosome core particle (NCP) containing 145 bp DNA, which revealed the same helical pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 79 publications
6
30
0
Order By: Relevance
“…The connection between histone and DNA dynamics was supported by comparing nucleosomes formed with the 601 sequence to those prepared with a tandem-repeat (TTAGGG) telomere sequence. The TTAGGG nucleosomes displayed a greater range of motions in the cluster network compared to the 601 nucleosomes consistent with previous experiments which showed that telomeric nucleosomes are less stable and wrap DNA less tightly ( Shi et al, 2020b ; Soman et al, 2020 ). Reduced nucleosome stability may translate into more flexible chromatin fibers that in turn enhance the potential for phase separation at telomeres ( Sanulli et al, 2019 ; Farr et al, 2021 ).…”
Section: Mas Nmr Of the Nucleosome Coresupporting
confidence: 90%
“…The connection between histone and DNA dynamics was supported by comparing nucleosomes formed with the 601 sequence to those prepared with a tandem-repeat (TTAGGG) telomere sequence. The TTAGGG nucleosomes displayed a greater range of motions in the cluster network compared to the 601 nucleosomes consistent with previous experiments which showed that telomeric nucleosomes are less stable and wrap DNA less tightly ( Shi et al, 2020b ; Soman et al, 2020 ). Reduced nucleosome stability may translate into more flexible chromatin fibers that in turn enhance the potential for phase separation at telomeres ( Sanulli et al, 2019 ; Farr et al, 2021 ).…”
Section: Mas Nmr Of the Nucleosome Coresupporting
confidence: 90%
“…This review commenced with a discussion of the classic B-DNA double helix structure; we conclude with two examples of studies on B-DNA deformations from ideality and how data from the PDB has complemented findings from other experimental and theoretical approaches. The B-DNA helix bending in the crystal structure ( 105 ) of a nucleosome comprising human telomeric DNA (with 23 (TTAGGG) repeats), in which the flexible d(TA) step, as well as d(TT) ones, plays an important role in facilitating the bending necessary for wrapping around the histone core, as shown in Figure 9 . DNA bending is related to minor groove width, which has been extensively studied in solution ( 106 ).…”
Section: The Importance Of the Pdb And Ndb For Studies On Dna Structure Flexibility And Functionmentioning
confidence: 99%
“…Clearly much more experimental structural data are needed before we have a comprehensive understanding of DNA flexibility.
Figure 9 The structure of the DNA component of a human telomeric nucleosome ( 105 ) , shown in space-filling representation with the two strands in separate colors, together with a magnified view of a typical region of DNA curvature, showing changes from ideality in base pair morphology such as roll, tilt, and twist .
…”
Section: The Importance Of the Pdb And Ndb For Studies On Dna Structure Flexibility And Functionmentioning
confidence: 99%
“…The accomplishment of genomic DNA activities in eukaryotic cells is propagated from the modulation of dynamic spatiotemporal organization of chromatin, which is achieved through factors including post-translational modifications (PTMs) ( Jenuwein and Allis, 2001 ; Bannister and Kouzarides, 2011 ; Bowman and Poirier, 2014 ; Fenley et al, 2018 ), incorporation histone variants ( Talbert and Henikoff, 2016 ; Martire and Banaszynski, 2020 ), remodelers, and other effector proteins ( Tyagi et al, 2016 ; Armeev et al, 2019 ; Reyes et al, 2021 ). Since the first atomic resolution structure was obtained 24 years ago ( Luger et al, 1997 ), well over a hundred structures of NCPs with different DNA sequences or histone variants and in complex with protein factors have been determined by X-ray diffraction (XRD) and cryogenic electron microscopy (cryo-EM) ( Luger et al, 1997 ; Korolev et al, 2018 ; Zhou et al, 2019 ; Soman et al, 2020 ; Lobbia et al, 2021 ). The atomic structure information opened the door to understanding the molecular basis of genomic DNA regulation processes.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of DNA in nucleosomes is one of the dominant factors dictating the architecture, compactness, and accessibility of chromatin. Varying DNA sequences lead to changes in nucleosome structure, dynamics, positioning, and compactness ( Shaytan et al, 2017 ; Shi et al, 2020b ; Soman et al, 2020 ). For example, our recent study revealed that the telomeric NCPs exhibit higher mobility in both histone N-terminal tails and core regions in comparison with the Widom 601 NCPs ( Shi et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%